Kelembagaan dan Operasionalisasi BUMDes Berbasis Syari’ah Perspektif Hukum Ekonomi Syari’ah - Hesim, Mohammad; Fathoni, M. Kamal; Alhusni, Alhusni; Sibawaihi, Muhammad (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
The purpose of this research is to find out about the institutional and operational system of BUMDes based on sharia. This research is also called normative-empirical research, because the focus of this research study is in the form of the concept of economic fiqh law/sharia economic law regarding BUMDes, rules and norms that are backgrounded by observations of phenomenology and field facts that occur. Phenomenology is an approach that seeks to enter into the world of meaning conceptualized in individuals or groups which is then manifested in the form of phenomena. The results of the study show that: 1) in carrying out the sharia-based BUMDes institutions, the thing that is considered by the village government and the community is maslahah al-mursalah which pays more attention to human welfare, especially the village community where the BUMDes is established in order to improve the quality of life of the community. 2) Operationalization of sharia-based BUMDes which is carried out on this sharia-based BUMDes is by using shirkah, ba'i, and mudharabah contracts. This is applied to every existing unit, and is very good to be a model for businesses that want to follow the sharia system in their operations.